1997
DOI: 10.1093/humrep/12.7.1531
|View full text |Cite
|
Sign up to set email alerts
|

Early cleavage of in-vitro fertilized human embryos to the 2-cell stage: a novel indicator of embryo quality and viability

Abstract: A number of non-invasive methods have been proposed to evaluate embryo viability in human in-vitro fertilization programmes. In addition to biochemical analyses, a common method for the selection of embryos prior to transfer involves assessment of embryo quality and morphology. We propose a new method to evaluate embryo viability based on the timing of the first cell division. Fertilized embryos that had cleaved to the 2-cell stage 25 h post-insemination were designated as 'early cleavage' embryos while the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
131
3
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(158 citation statements)
references
References 26 publications
10
131
3
14
Order By: Relevance
“…Such restrictions inevitably result in the loss of the ability to apply selective criteria when choosing embryos for transfer. Criteria such as morphology and cleavage rate [13], and timing of the first cleavage division [14][15][16] have been applied succesfully to select early cleavage stage embryos with enhanced implantation potential for transfer. This approach is only realistically feasible, however, when it is possible to cryopreserve the remaining embryos in a cohort which are not chosen for transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Such restrictions inevitably result in the loss of the ability to apply selective criteria when choosing embryos for transfer. Criteria such as morphology and cleavage rate [13], and timing of the first cleavage division [14][15][16] have been applied succesfully to select early cleavage stage embryos with enhanced implantation potential for transfer. This approach is only realistically feasible, however, when it is possible to cryopreserve the remaining embryos in a cohort which are not chosen for transfer.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, many criteria for embryo selection have been proposed in the field of assisted reproductive technology (ART) [1][2][3][4][5][6][7]. Among of these criteria, morphologic features have been used extensively in selecting good-quality embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Several oocyte, zygote, and cleavage-stage grading methods that were not used in this study have been shown to correlate with an embryo's implantation potential (1)(2)(3)(5)(6)(7)11,12,28,(30)(31)(32)(33)(34)(35)(36)(37). Tesarik et al (1) showed that the relationship between the number of embryos transferred and the multiple rate depended on PN-S morphology; transfer of 2 embryos from pattern zero zygotes usually resulted in a twin pregnancy.…”
Section: Discussionmentioning
confidence: 74%
“…New methods under evaluation include number, pattern, and distribution of nucleoli within the PN (1,2,5,7), size and shape of PN-S halos (7), early cleavage to the 2-cell stage (32,36,37), day-3 fragmentation pattern (35), and variation in the thickness of the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%